Bioactive Constituents And Antimicrobial Activity Of Cell Cultures Of Azadirachta Indica - RAMESH K. SATDIVE; SUSAN EAPEN; DEVANAND P. FULZELE (International Journal of Pharma and Bio Sciences, 2011)
The present study describes the major content and antimicrobial activity of Azadirachta indica cell culture extracts. Major constituents of cell culture extracts were evaluated by HPLC and chromatographic analysis revealed that highest concentrations of azadirachtin (0.0069 % dry wt) synthesised by multiple shoot cultures. The results showed that multiple shoot cultures synthesised 17-fold more azadirachtin compared to callus cultures. Cell cultures and plant materials were extracted with methanol, ethanol and petroleum ether that exhibited antimicrobial activity. Of the various solvent used, methanol extracts was exhibited better antimicrobial activity whilst petroleum ether extracts found ineffective. Bark and leaves extracts showed higher antimicrobial activity by minimum inhibitory concentration (MIC) compared to in vitro cell cultures extracts. Bark extracts showed maximum MIC against Staphyloccocus aureus followed by Bacillus subtilis whereas shoot culture extracts showed maximum MIC against Pseudomonas aeruginosa followed by somatic embryos and callus culture extracts. On the basis of these results we therefore suggested that in vitro cell cultures contain potential active antimicrobial components